PERANCANGAN ALAT PEMESANAN MAKANAN DI RESTORAN SECARA WIRELESS - Susila, Tjandra; Winata, Tony; Nugroho, Rakhman Setyo (TESLA Jurnal Teknik Elektro UNTAR, 2006)
To keep the quality ambiguous / vague meaning and reputation, a restaurant must have good service to satisfy its customer. Based on this consideration, so it is necessary to make a menu ordering device in a restaurant build in wireless communication that can be adjusted by programming the device. By using this device, a restaurant, can improve its quality along with reputation and minimize menu ordering error problems.